A Survey on Sentiment Analysis and Mining of Opinions using Natural Language Processing Techniques - Kaur, Amanpreet; Kaur, Prabhpreet (International Journal of Computer Sciences and Engineering, 2025)
In the past few years, sentiment analysis received a great attention as the mining of opinions or reviews from the customer about the product or object. Mining of opinions is defined as a computational task for reviewing the emotions, attitudes and opinions of an individual about a particular product. It evaluates the results as positive, negative or neutral. Before buying a product, the customers want to know the reviews of other users about that product. To make the product more profitable and other future determinations, customer feedback about the product are analyzed by the companies. So the sentiment analysis is decisive for both individuals and companies for making certain decisions. Now a day‘s opinion mining is most prominent branch of research in the area of text mining. This survey deals with a detail study of sentiment analysis, opinion mining and natural language processing techniques used for sentiment analysis. Some existing work that has been done in past few years has also been discussed in this survey.